Development in plasma surface diffusion techniques of Ti-6Al-4V alloy: a review - Xing, Ya-Zhe; Wang, Gui; Zhang, Yong; Chen, Yong-Nan; Dargusch, Matthew (International journal of advanced manufacturing technology, 2017)
Ti-6Al-4V alloy has been widely used as an important structural material in aerospace, automotive, and chemical and biomedical industries due to its high specific strength and excellent corrosion resistance. However, the poor tribological properties and low resistance to high temperature oxidation limit extensive applications of the alloy. Plasma surface diffusion treatments, including plasma carbonizing, plasma nitriding, and plasma alloying treatments, contribute to improve wear resistance and the anti-oxidation property of the alloy by introducing other elements into the surface of the alloy to form hard surface layers under low pressure conditions. In this review article, the developments in microstructure and properties of the layers generated by the three techniques were reviewed systematically. In particular, the development in the phase determination of the plasma-nitrided layer was analyzed. New approaches in accelerating the diffusion of atoms and optimizing process were analyzed in detail.